Selected NGOs and Poverty Reduction in Makurdi Local Government Area of Benue State, Nigeria - Vincent Iorja Gisaor (International Journal of Community Service & Engagement, 2021)
The research was undertaken to access the impact of Non-Government organizations (NGOs) on poverty reduction in Makurdi local government area of Benue State. Using descriptive approach to analyze the primary data obtained from the respondents through a structured questionnaires and semi-structured interview administered to the staff and officials of selected NGOs in the study area. Result shows that the respondents confirm benefits in terms of increased income, use of good transportation means, good accommodation, feeding and sleeping materials. Despite these benefits, there were challenges confronting the NGOs in the study area. One of the biggest challenges was finance to execute all their programmes as well as disburse to beneficiaries as loans and grants. The activities of NGOs were found only limited to Makurdi while the majority of the people were residing outside the state capital. Therefore, recommendations made include: awareness creation for more participation by people in entrepreneurship and financial independence since it is only through such skills that they can propel themselves out of poverty and the NGOs should seek for more sources of funding including soliciting financial support from the international community to enable it fund diversified economic activities of the vulnerable people in the country.